Efficient saccharification of ionic liquid-pretreated rice straw in a one-pot system using novel metagenomics derived cellulases. (February 2022) - Maleki, Morteza; Ariaeenejad, Shohreh; Salekdeh, Ghasem Hosseini
Graphical abstract: Highlights: Two novel ionic liquid tolerant cellulases were discovered from metagenomic data. The stability of the cellulases is enhanced in the presence of ionic liquid. Ionic liquid-activated rice straw was enzymatically hydrolyzed in the one-pot system. Abstract: Ionic liquids (ILs)-resistant cellulase enzymes can facilitate the saccharification of IL- pretreated biomass in a one-pot wash-free method. Using a bioinformatics approach, two cellulases, Persicel7 and Persicel8, with convincing evidence for ionic liquid tolerance were identified. Subsequently, these enzymes were heterologously expressed and biochemically characterized. Persicel7 and Persicel8 exhibited endo -β-1, 4-glucanase activity and were resistant to inhibitors and several organic solvents. Their activity in 10% (v/v) 1-ethyl-3-methylimidazolium chloride and 1-butyl-3-methylimidazolium chloride were 130% higher compared with IL-free control. The half-life of cellulases was improved up to 11-fold when incubated with 20% (v/v) solution of ion liquids. In addition, a one-pot IL-pretreatment and enzymatic saccharification of rice straw enhanced the saccharification rate by 33% compared to the untreated reaction. The Persicel7 and Persicel8 unique properties make them attractive candidates for industrial applications, particularly hydrolyzing ion liquid activated biomass in a one-pot system.